Correspondence Time as an Alternative Plane: Togetherness, Encounter, Virtuality - Jonutytė, Jurga (Tautosakos darbai, 2025)
The article is based on a mutual correspondence by a married couple, written in the middle of the 20th century to and from the places of imprisonment. The aim is revealing, with the help of this correspondence, the role of the common letter as an artefact maintaining the relationship between these close people, and its capacity of creating the virtual common duality of time. The notion of time in this article focuses on simultaneity (Alfred Schutz); however, the author demonstrates how written correspondence on paper creates a special kind of this temporary modus. Handwritten letters display traces of movement left by their author’s hand, thus enabling a peculiar experience of intercorporeality, or a bodily presence of another person (Tim Ingold). Therefore, rather than just conveying the meaningful content, they are capable of infecting the reader with their author’s state of mind (the notion of infection here is borrowed from Eric Landowski). The practice of corresponding enabled its participants to distance themselves from the real time and space (that is, from the painful surroundings of imprisonment), and to move into the virtual time (Henri Bergson, Gilles Deleuze). The author maintains that, rather than signifying uncertainty, illusion or mistake, such virtuality may be perceived as a readily available, benevolent status of mind, which is typical for humans finding themselves in painful situations, and familiar to many. The author also discusses the ethical and methodical issues raised by researching such kind of material. She concludes that if the material is enabled to speak first (Maria Tamboukou), its details leave traces that can be followed and interpreted, enabling us to broaden our understanding of this human activity (Adriana Cavarero, Hanna Meretoja).
Keywords: letter; simultaneity; narrative unconsciousness; virtuality